Riwayat Mendapat Konseling Tentang IVA Berhubungan dengan Keikutsertaan IVA pada Wanita Usia Subur di Puskesmas Sedayu I dan Sedayu II Bantul - Arantika Meidya Pratiwi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Cervical cancer is a health problem that hit countries in the world. WHO estimates there are 460,000 new cases worldwide and 75% are in developing countries. The incidence of cervical cancer in Indonesia according to the Indonesia Departement of Public Health in 2010 reached 100 per 100,000 population per year. In contrast to the developed countries, the incidence and mortality from cervical cancer has decreased due to cervical cancer screening program that can be done with a pap smear or VIA (Visual Inspection of the Uterine Cervix with Acetic Acid). Based on the results of a survey conducted among women of childbearing age in Sedayu I and II Bantul Local Government Clinic in the last 3 years, it was found that the amount of data women of childbearing age inspecting VIA continues to decrease each year. The aim of research to determine the relationship between a history of getting counseling about VIA and VIA participation in women of childbearing age in Sedayu I and II Bantul Local Government Clinic. This study uses an analytical survey. The design of this study using cross sectional. The population in this study are all of women of childbearing age at Sedayu I and Sedayu II Local Government Clinic. The number of samples taken by counting the estimated number of samples obtained 102 women of childbearing age. The results showed that most of women of childbearing age ever get counseling from midwife/health workers about VIA as many as 65 people (63.7%) and the remaining 37 (36.3%). A total of 60 women of childbearing age (58.8%) has audited women of childbearing age VIA test and 42 (41.2%) have never done VIA test. The conclusion there was signiﬁ cance correlation between a history of getting counseling about VIA and the VIA participation in women of childbearing age in Sedayu I and II Bantul Local Government Clinic with value of p=0.000.